GE_GERICHTE P/1520/2011 vom 30. Oktober 2014 - GE Cour de justice (2014)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT; CONTRAINTE SEXUELLE; TENTATIVE(DROIT PÉNAL); CONCOURS D'INFRACTIONS | CP.187; CP.189; CP.22; CP.49